Design of a nanozyme-based magnetic nanoplatform to enhance photodynamic therapy and immunotherapy - Chen Bai; Jiajing Liu; Luyao Bai; Dapeng Yao; Xiaofeng Li; Haoran Zhang; Dong Guo (Elsevier, 2024)
The tumor microenvironment, particularly the hypoxic property and glutathione (GSH) overexpression, substantially inhibits the efficacy of cancer therapy. In this article, we present the design of a magnetic nanoplatform (MNPT) comprised of a photosensitizer (Ce6) and an iron oxide (Fe3O4)/manganese oxide (MnO2) composite nanozyme. Reactive oxygen species (ROS), such as singlet oxygen (1O2) radicals produced by light irradiation and hydroxyl radicals (·OH) produced by catalysis, are therapeutic species. These therapeutic substances stimulate cell apoptosis by increasing oxidative stress. This apoptosis then triggers the immunological response, which combines photodynamic therapy and T-cell-mediated immunotherapy to treat cancer. Furthermore, MNPT can be utilized as a contrast agent in magnetic resonance and fluorescence dual-modality imaging to give real-time tracking and feedback on treatment.